Surface Functionalization And Characterization Of Antimicrobial Porous P(3hb-Co-4hb) Scaffold With Collagen Peptide For Biomedical Applications - Gurusamy, Tana Poorani (2020)
P(3-hydroxybutyrate-co-4-hydroxybutyrate), [P(3HB-co-4HB)] is a bacterial derived biopolymer known for its high levels of biocompatability. However, surface of P(3HB-co-4HB) is found to be hydrophobic with minimal recognition sites for cell attachment. This makes it less desirable candidate to be tailored as scaffolds for tissue engineering and biomedical applications. Due to this, this research was undertaken to fabricate P(3HB-co-4HB) with collagen peptides scaffolds using physiochemical modifications to further enhance their surface wettabilty as well as to support cell growth for biomedical applications. In this case, a bacterial strain, Cupriavidus malaysienesis sp. USMAA 1020 transformant, was found to synthesize P(3HB-co-4HB) from 4-hydroxybutyrate (4HB) precursor substrates, namely 1,4-butanediol and 1,6-hexanediol, respectatively. Firstly, a porous P(3HB-co-4HB) was fabricated through salt leaching and freeze drying techniques. This was then followed by the incorporation of collagen peptides at various concentrations (2.5 wt% - 12.5 wt%) to P(3HB-co-4HB) using two different modifications technique, amiolysis and collagen-coating. As a result, three types of P(3HB-co-4HB) scaffolds was fabricated including silver sulfadiazine(SSD) coated/collagen peptide-coated P(3HB-co-4HB) scaffolds, silver sulfadiazine blend/collagen peptide-coated P(3HB-co-4HB) scaffold and silver sulfadiazine blend/aminolysed P(3HB-co-4HB).